H [infinity] controller synthesis for sampled-data systems and nonlinear systems - Yu, Qi. (2011)
In this project, we first investigate the H∞ synthesis problem for a class of sampleddata control systems. We consider both Zero-Order Hold (ZOH) and Generalized Sample and Hold Functions (GSHF). Explicit formulae for such Hoc sampled-data controllers in case of linear time-invariant plants are given. Secondly, we examine the robustness of the Hoc controlled systems. It is shown that the sampled-data H∞ controller cannot achieve the same system's performance as the continuous-time controller does. However, by varying the sampling period, we show that sampled-data H∞ controller can reach a robustness level close to what a continuous-time H∞ controller can achieve when the sampling period is small enough. Furthermore, with the proposed GSHF-based controller, better robustness is obtained for the H∞ synthesis system in comparison with the ZOH-based controller.